U.S. News Coverage of Global Terrorist Incidents. Issue 6 (2nd November 2017) - Sui, Mingxiao; Dunaway, Johanna; Sobek, David; Abad, Andrew; Goodman, Lauren; Saha, Paromita
Abstract : A slew of gruesome executions by terrorist groups in 2014–2015 renewed interest in the public relations strategies of terrorists. As a case in point, the Islamic State group's escalating brutality reflects their efforts as a relatively nascent extremist group to ensure a high and sustained volume of media coverage, especially among Western outlets. But what characteristics of events actually prompt coverage from major U.S. news media? Using a rich data set of terrorist incidents and coverage from six major broadcast and cable U.S. networks, we model coverage of terrorist incidents as a function of event proximity from U.S. soil, target country affinity with the United States, number of total and U.S. casualties, and the characteristics of the terrorist group. Our findings largely corroborate expectations set forth by the literature on norms and routines of journalism and economics of news. When it comes to terrorism, coverage by U.S. major media outlets is largely dependent on proximity to and affinity with the United States, weapons of mass destruction, and the number of global and U.S. casualties.